2018
DOI: 10.1261/rna.068395.118
|View full text |Cite
|
Sign up to set email alerts
|

Apobec1 complementation factor (A1CF) and RBM47 interact in tissue-specific regulation of C to U RNA editing in mouse intestine and liver

Abstract: Mammalian C to U RNA is mediated by APOBEC1, the catalytic deaminase, together with RNA binding cofactors (including A1CF and RBM47) whose relative physiological requirements are unresolved. Although A1CF complements APOBEC1 for in vitro RNA editing, A1cf -/mice exhibited no change in apolipoproteinB (apoB) RNA editing, while Rbm47 mutant mice exhibited impaired intestinal RNA editing of apoB as well as other targets. Here we examined the role of A1CF and RBM47 in adult mouse liver and intestine, following del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 44 publications
6
58
0
Order By: Relevance
“…It is clear that human A1CF can mediate APO1 editing activity on APOB RNA in this cellbased assay system, but its effectiveness on activity is about 73% of RBM47; this trend is consistent with the relative impact that knockout of mouse A1cf and Rbm47 has on Apob editing activity in vivo as was recently reported [27]. This same trend was observed when testing the mouse homologs of these proteins with this cell-based assay system, although mA1CF was observed to be slightly weaker for aiding APOB editing activity: mA1CF is only about 52% as effective at inducing editing as mRBM47.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is clear that human A1CF can mediate APO1 editing activity on APOB RNA in this cellbased assay system, but its effectiveness on activity is about 73% of RBM47; this trend is consistent with the relative impact that knockout of mouse A1cf and Rbm47 has on Apob editing activity in vivo as was recently reported [27]. This same trend was observed when testing the mouse homologs of these proteins with this cell-based assay system, although mA1CF was observed to be slightly weaker for aiding APOB editing activity: mA1CF is only about 52% as effective at inducing editing as mRBM47.…”
Section: Discussionsupporting
confidence: 90%
“…For the most part, this data correlates well with what has been suggested by mouse in vivo studies on substrate specificity of the two cofactors [27], and many of the substrates shown to be favored by RBM47 in that past work were similarly favored here. However, a few key differences stand out.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations